Metformin inhibits the apoptosis of intervertebral disc tissue cells in rabbit model with lumbar intervertebral disc degeneration - DONG Junli, CAI Shaokang, YAN Lei, CAI Yi (Jichu yixue yu linchuang, 2023)
Objective To investigate the impacts of metformin on autophagy and inflammation of intervertebral disc tissue in rabbits, so as to preliminarily explore the molecular mechanism of its anti-intervertebral disc degeneration. Methods The rabbits were diveded into: sham operation group, model group, metformin group, autophagy inhibitor group and metformin + autophagy inhibitor group, with 10 rabbits in each. The positive expression of autophagy-related protein 7 (Atg7) was measured by immunohistochemical staining; The expression of autophagy-related proteins LC3Ⅱ, Beclin1, lysosome-associated membrane protein 2 (LAMP2), tumor necrosis factor-α (TNF-α), IL-1β, and apoptosis-related protein caspase-8 was measured by Western blot. Results Compared with the model group, the intervertebral disc degeneration of the rabbits in the metformin group was alleviated; The formation of autophagosomes and autolysosomes increased. The expression of autophagy proteins increased; And the expression of inflammation and apoptosis proteins decreased (PPConclusions Metformin may inhibit the apoptosis of intervertebral disc tissue and improve intervertebral disc degeneration by promoting autophagy activation and attenuating inflammatory response.